Once-monthly injection of paliperidone palmitate in patients with recently diagnosed and chronic schizophrenia: a post-hoc comparison of efficacy and safety. (22nd November 2017) - Si, Tianmei; Zhuo, Jianmin; Turkoz, Ibrahim; Mathews, Maju; Tan, Wilson; Feng, Yu
ABSTRACT: Background : The use of long-acting injectable antipsychotics in recently diagnosed schizophrenia remains less explored. We evaluated the efficacy and safety of paliperidone palmitate once-monthly (PP1M) treatment in adult patients with recently diagnosed vs. chronic schizophrenia. Research design and methods : These post-hoc analyses included two multicenter studies. Study 1 (NCT01527305) enrolled recently diagnosed (≤5 years) and chronic (>5 years) patients; Study 2 (NCT01051531) enrolled recently diagnosed patients only. Recently diagnosed patients were further sub-grouped into ≤2 years or 2–5 years. The primary efficacy endpoint was the change from baseline in Positive and Negative Syndrome Scale (PANSS) total score. Results : In Study 1, 41.5% patients had recent diagnosis (≤2 years: 56.8%; 2–5 years: 43.2%); 58.5% had chronic schizophrenia. In Study 2, 52.8% and 47.2% patients were grouped into ≤2 years and 2–5 years, respectively. PANSS total score showed significantly greater improvement in patients with recently diagnosed vs. chronic schizophrenia. Similar results were obtained for PANSS responder rate, improvements in PANSS, and CGI-S scores. Conclusion : PP1M was efficacious in both recently diagnosed and chronic schizophrenia, with the benefits being more pronounced in patients with recently diagnosed schizophrenia. This adds to growing evidence recommending long-acting antipsychotic interventions at early stages of schizophrenia.